Hillslope Topography Mediates Spatial Patterns of Ecosystem Sensitivity to Climate. Issue 2 (17th February 2018) - Hoylman, Zachary H.; Jencso, Kelsey G.; Hu, Jia; Martin, Justin T.; Holden, Zachary A.; Seielstad, Carl A.; Rowell, Eric M.
Abstract: Understanding how hillslope topography modulates ecosystem dynamics across topoclimatic gradients is critical for predicting future climate change impacts on vegetation function. We examined the influence of hillslope topography on ecosystem productivity, structure, and photosynthetic activity across a range of water and energy availability using three independent methods in a forested watershed (Montana, USA): 308 tree cores; light detection and ranging quantification of stem density, basal area, foliar biomass, and total biomass; and the enhanced vegetation index (EVI; 1984–2012). Multiple linear regression analysis across three conifer species revealed significant increases in measured basal area increment growth rates (from 56 to 2, 058 mm 2 /yr) with increasing values of the topographic wetness index and decreases in the climatic water deficit. At the watershed scale, we observed strong gradients in total biomass (e.g., 52 to 75 Mg/ha), which increased from ridgelines to convergent hollows. The most predominant topographic organization of forest biomass occurred along locations of climatically driven water limitations. Similarly, an analysis of growing season EVI indicated enhanced photosynthetic activity and a prolonged growing season in convergent hillslope positions. Collectively, these analyses confirm that within water‐limited landscapes, meter‐scale differences in topographic position can mediate the effects of the local energy balance and contribute to large differences in local hydrometeorological processes that are a necessary consideration for quantifying spatial patterns of ecosystem productivity. Further, they suggest that local topography and its topology with regional climate may become increasingly important for understanding spatial patterns of ecosystem productivity, mortality, and resilience as regional climates become more arid. Key Points: Ecosystem productivity was more sensitive to hillslope convergence and divergence than spatial patterns of topoclimate Spatial patterns of ecosystem productivity become highly organized by topographic convergence as climatic water limitations intensify Hillslope convergence leads to enhanced and sustained photosynthetic activity across gradients in topoclimate